Ethnomedicine and Culture: Exploitation of plant species for traditional use in the remote area of Kashmir Himalayas - Khoja, Aadil Abdullah; Andrabi, Syed Asif Hussain; Mir, Rayees Afzal; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2022)
Introduction: In the valley of Kashmir-India, use of flora is not only prioritized over fauna species to get against health disorders but plays a vital role in the cultural aspects. The uses of herbs, particularly those that have a scientific basis as remedy of minor illnesses are progressively appreciated across the modern world. Methods: The present study was conducted from March 2019 to August 2021 for the collection of medicinally important plants and related traditional knowledge in the frontier administrative district (Kupwara) of Kashmir- India. A simple stratified sampling using semi structured interviews followed by group discussions was employed to achieve the goal. Results: A total of 53 plant species belonging to 36 families, with Asteraceae as the dominant family (11%) were recorded. The most dominant life form used in the treatment of various ailments were herbs with 42 species (79%), followed by trees (6 species, 11%), shrubs (3, 6%), ferns and fungi (1 species each). Roots were most frequently used (39%), followed by leaves (21%), tuber, stem latex, whole plant (5% each), wood, fruits (3% each), fruit, bark, seed, fruiting body, twig and whole frond (2% each). The ICF (Informant Consensus Factor) values ranged from 0.95 to 0.98, and the highest ICF was recorded for gastrointestinal disorders, liver diseases, bone and joint disorders, dental diseases and kidney problems (0.98 each), while as the lowest values of ICF were recorded for ethno-veterinary diseases (0.95). Gastro-intestinal disorders were treated with most species (22%). Highest Use Value (UV) was recorded for Artemisia absinthium while lowest values of UV were recorded for Eryngium billardieri. A cross-cultural comparison of plant resources shows that 41 plants were commonly used by all ethnic groups. Upon the similarity of usage, Gujjars and Bakarwals (26%) showed greater similarity, whereas the least overlap was observed between Kashmiri and Bakarwal (9%). Cluster analysis yielded two primary clusters, cluster first included the plant species with medicinal (Med) attributions and Cluster 2 comprised the species with a variety of attributions like food, fodder, spice, black magic (bla-mag); herbal tea (her-tea) and fuel wood (fue-wod). The highest FUV (Family Use Value) was reported for Pinaceae (0.49) followed by Asteraceae (0.47) and Polygonaceae (0.46). The results in this study have listed some of the medicinal plants like, Rhodiola fastigiata, Lilium polyphyllum, Betula utilis and Anagallis arvensis reported for the first time with traditional usage. Conclusion: The present study reveals the importance of the plants across the frontier administrative district (Kupwara) of Kashmir- India. The use of local plants for medicinal purposes and other traditional uses are being practiced from generations; in this regard species with high UV can be bio-profiled for the possible elucidation of some novel molecule with potent medicinal attribution. Keywords: Plants, medicinal, Use Value, cross-culture